2013
DOI: 10.2174/1566524011313060015
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Alterations by Aldosterone During Hypertension: From Clinical Observations to Genomic and Non-Genomic Mechanisms Leading to Vascular Damage

Abstract: Hypertension is traditionally considered a disease in which elevated blood pressure contributes to inflammation and activation of the immune system, leading to cardiovascular injury and end-organ damage. Here, we discuss the effects of aldosterone on the immune system and aldosterone's contribution to vascular pathogenesis. Studies in human have suggested a broader role for aldosterone, beyond elevating blood pressure. Recent clinical data support the notion that aldosterone can directly alter the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…The pathogenesis of AHT involves the renal, vascular, and endocrine systems ( 12 15 ), affecting mainly sodium-water reabsorption and arterial vasoconstriction. Pathological conditions, such as primary aldosteronism (PA), are responsible for up to 5–10% of patients diagnosed with AHT, and involve an increased production of aldosterone that leads to AHT, cardiovascular damage, heart diseases ( 16 18 ), and renal and immune alterations ( 19 23 ). Aldosterone is a mineralocorticoid hormone with non-genomic and genomic actions; the latter through the mineralocorticoid receptors (MR) can alter sodium transport in renal collecting ducts, increase water uptake, blood volume, and eventually raise blood pressure.…”
Section: Arterial Hypertension (Aht)mentioning
confidence: 99%
“…The pathogenesis of AHT involves the renal, vascular, and endocrine systems ( 12 15 ), affecting mainly sodium-water reabsorption and arterial vasoconstriction. Pathological conditions, such as primary aldosteronism (PA), are responsible for up to 5–10% of patients diagnosed with AHT, and involve an increased production of aldosterone that leads to AHT, cardiovascular damage, heart diseases ( 16 18 ), and renal and immune alterations ( 19 23 ). Aldosterone is a mineralocorticoid hormone with non-genomic and genomic actions; the latter through the mineralocorticoid receptors (MR) can alter sodium transport in renal collecting ducts, increase water uptake, blood volume, and eventually raise blood pressure.…”
Section: Arterial Hypertension (Aht)mentioning
confidence: 99%
“…También, estudios recientes han demostrado que la aldosterona puede afectar al sistema inmune modulando la actividad de células dendríticas que inducen la activación y polarización de linfocitos T a Linfocitos Th17 que producen interleukina 17, la cual se ha relacionado con enfermedades autoinmunes (Munoz-Durango et al 2013;Munoz-Durango et al 2015).…”
Section: El Hiperaldosteronismo Primariounclassified
“…2008). *** El punto de corte superior para la razón F/E es variable para adultos y niños, valor que puede aumentar con la edad en sujetos normotensos (Campino et al 2013).…”
Section: Contribuciones Y Reconocimientosunclassified
“…Currently, the physiopathology of cardiovascular diseases, such atherosclerosis [ 63 ] and hypertension, are considered to be closely related with inflammatory processes [ 64 , 65 ]. As a result, inflammatory cells infiltrate the tissues producing proinflammatory cytokines and inducing the generation of oxidative stress, which leads to fibrosis and end-organ damage [ 18 ]. The Renin-Angiotensin-Aldosterone System (RAAS) has been closely related with the deleterious effect seen in patients with cardiovascular diseases, turning RAAS into an important axis that could be intervened to reduce disease [ 17 , 18 ].…”
Section: Clinical Evidence Associating the Mr With The Modulation mentioning
confidence: 99%
“…In the context of the immune response, it has been consistently reported that aldosterone stimulation promotes proinflammatory responses in various tissues [ 17 , 18 ]. In human leucocytes, MR expression has been reported in CD34+ hematopoietic progenitor, also in peripheral blood T and B lymphocytes, monocytes, and neutrophils [ 19 ].…”
Section: Introductionmentioning
confidence: 99%